Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.

Changing openness and tolerance towards LGBTQ singer-songwriters - Williams, Katherine (The Cambridge Companion to the Singer-Songwriter, 2016)
Most often associated with modern artists such as Bob Dylan, Elton John, Don McLean, Neil Diamond, and Carole King, the singer-songwriter tradition in fact has a long and complex history dating back to the medieval troubadour and earlier. This Companion explains the historical contexts, musical analyses, and theoretical frameworks of the singer-songwriter tradition. Divided into five parts, the book explores the tradition in the context of issues including authenticity, gender, queer studies, musical analysis, and performance. The contributors reveal how the tradition has been expressed around the world and throughout its history to the present day. Essential reading for enthusiasts, practitioners, students, and scholars, this book features case studies of a wide range of both well and lesser-known singer-songwriters, from Thomas d'Urfey through to Carole King and Kanye West.